Efektivitas Pelayanan Digitalisasi Kartu Prakerja di Dinas Tenaga Kerja Koperasi dan UKM di Kota Gorontalo - Artawanda Pakaya; Rustam Tohopi; Alexander H. Badjuka (Perspektif Administrasi Publik dan hukum, 2026)
This study aims to analyze the effectiveness of digitalized Pre-Employment Card services at the Department of Manpower, Cooperatives, and SMEs of Gorontalo City. The study is motivated by the ongoing transformation of digital-based public services, which requires improvements in the quality of information, consultation, and assistance provided to the public regarding the Pre-Employment Card Program. A qualitative approach with a descriptive design was employed. Data were collected through interviews, observations, and documentation involving the Head of the Department, heads of relevant divisions, implementing staff, and participants of the Pre-Employment Card Program. Data were analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The study adopted Agus Dwiyanto's (2006) theory of service effectiveness, which includes the indicators of productivity, service quality, responsiveness, responsibility, and accountability. The findings reveal that the digitalized Pre-Employment Card services have generally been implemented effectively. Government personnel were able to provide timely information and assistance, while service quality was reflected in courteous interactions, transparent information, and accessible digital services. In terms of responsibility and accountability, service implementation complied with established procedures and remained publicly accountable. However, several challenges persist, particularly the limited public understanding of the procedures for using the digital platform. Therefore, broader public outreach, improved human resource capacity, and the optimization of digital infrastructure are recommended to further enhance service effectiveness and support the delivery of high-quality digital public services in the future.